Environmental conditions inducing black-point symptoms in durum wheat - Desclaux D. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
Taking into account black-point susceptibility in a screening test lead to a better knowledge of the factors involved. Abiotic factors such as humidity or temperature contribute to inducing black-point and modelisation of their interactions allows threshold values to be determined.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)